2022
DOI: 10.1101/2022.01.26.22269729
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sputnik-V reactogenicity and immunogenicity in the blood and mucosa: a prospective cohort study

Abstract: Background: Sputnik-V (Gam-COVID-Vac) is a heterologous, recombinant adenoviral (rAdv) vector-based, COVID-19 vaccine now used in >70 countries. Yet there is a shortage of data on this vaccine's performance in diverse populations. Here, we performed a prospective cohort study to assess the reactogenicity and immunologic outcomes of Sputnik-V vaccination in a multi-ethnic cohort from Kazakhstan. Methods: COVID-19-free participants (n=82 at baseline) were followed at day 21 after Sputnik-V dose 1 (rAd5) and d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Firstly, from our assessment of reactogenicity, we observed overall low severity of adverse events in both trial arms, with local injection site being the most common adverse event. This result is comparable to adverse events documented in other reports comparing homologous and heterologous boosting (9,13,(17)(18)(19), and each vaccine independently (20,21). The incidence of adverse events was consistently higher in those aged <40 years, which is a common trend in SARS-CoV-2 vaccination studies (20,22).…”
Section: Discussionsupporting
confidence: 86%
“…Firstly, from our assessment of reactogenicity, we observed overall low severity of adverse events in both trial arms, with local injection site being the most common adverse event. This result is comparable to adverse events documented in other reports comparing homologous and heterologous boosting (9,13,(17)(18)(19), and each vaccine independently (20,21). The incidence of adverse events was consistently higher in those aged <40 years, which is a common trend in SARS-CoV-2 vaccination studies (20,22).…”
Section: Discussionsupporting
confidence: 86%
“…AZD1222 vaccinees who experienced breakthrough infections displayed robust anamnestic IgG responses, which correlated with reduced viral loads and durations of viral shedding in saliva. Although we and others have observed transient increases in NELF IgA levels from vaccinees with prior SARS-CoV-2 infection (22,41,43), intramuscular vaccination with adenovirus-and mRNA-based COVID-19 vaccines does not appear to induce anamnestic NELF IgA responses in SARS-CoV-2-seronegative vaccinees despite eliciting IgA responses in serum (43)(44)(45). These findings suggest that different approaches (e.g., use of adjuvants, other delivery routes) will be required to improve mucosal immunogenicity for currently licensed COVID-19 vaccines (46).…”
Section: Discussionmentioning
confidence: 70%
“…Our study revealed a higher prevalence of previous COVID-19 infections among vaccinated individuals when compared to the unvaccinated ones. One potential hypothesis for this observation could be the risk of breakthrough infections following vaccination, particularly noted with inactivated whole virus vaccines such as BBIBP-CorV [40,41] and Gam-COVID-Vac [42]. Additionally, vaccine hesitancy, often accompanied by a denial of the virus's existence or the severity of the disease, may contribute to underreporting of infection rates within the unvaccinated population [43].…”
Section: Discussionmentioning
confidence: 99%